Colony morphology and molecular identification of Vibrio spp. on green mussels (Perna viridis) in Yogyakarta, Indonesia tourism beach areas - FARIDA HIKMAWATI; Ari Susilowati; RATNA SETYANINGSIH (Society for Indonesian Biodiversity, 2019)
Abstract. Hikmawati F, Susilowati A, Setyaningsih R. 2019. Colony morphology and molecular identification of Vibrio spp. on green mussels (Perna viridis) in Yogyakarta, Indonesia tourism beach areas. Biodiversitas 20: 2891-2899. Green mussels (Perna viridis) have filter feeder properties that allow pathogenic bacteria from the water environment to accumulate in relatively high levels. About 20% of foodborne diseases are caused by large quantities of seafood contaminated with bacteria. The purpose of this study is to determine the morphological characteristics, pathogenicity, identity, and the kinship of Vibrio species on green mussels in Yogyakarta coastal tourism areas. Vibrio spp. were grown on selective differential TCBS media. In this media, the suspected Vibrio spp. would produce yellow or green colonies. The ability of hemolysis of Vibrio was blood agar media, the species was molecularly identified using 16S rRNA gene sequence, and the phylogenetic relationship of the Vibrio spp., was analyzed using MEGA X Neighbor-Joining program. Based on morphological analysis, we obtained 23 bacterial isolates suspected to be Vibrio spp. Two Isolates (L1K2 6 and L2K2 13) were positive for ?-hemolysis activity and 4 isolates (L1K1 3, L2K1 8, L2K2 16, and L3K2 22) were positive for ?-hemolysis activity. The molecular analysis involved 18 Vibrio species, and 4 of them represented the Vibrio genus and 14 species represented 97-99% similarity species in accordance with the 16S rRNA sequence in database, namely: Vibrio alginolyticus, Vibrio parahaemolyticus, Vibrio cholerae, Vibrio neocaledonicus, Vibrio mimicus, Vibrio azureus, Vibrio diabolicus, Vibrio tapetis, Vibrio natriegens, and Vibrio owensii. The most dominant number of Vibrio isolates was V. alginolyticus, while the lowest was V. owensii. The highest number of Vibrio species in green mussels was found in Goa Cemara beach while the lowest was in Kwaru beach. Vibrio spp bacteria found in green clams in coastal tourism areas in Yogyakarta have close phylogenetic relationships with other Vibrio in seafood in Indonesian coastal waters.